Speeding up chromosome evolution in Phaseolus: multiple rearrangements associated with a one-step descending dysploidy - Fonsêca, Artur; Ferraz, Maria Eduarda; Pedrosa-Harand, Andrea (Chromosoma, 2016)
The genus Phaseolus L. has been subject of extensive cytogenetic studies due to its global economic importance. It is considered karyotypically stable, with most of its ca. 75 species having 2 n = 22 chromosomes, and only three species ( Phaseolus leptostachyus , Phaseolus macvaughii , and Phaseolus micranthus ), which form the Leptostachyus clade, having 2 n = 20. To test whether a simple chromosomal fusion was the cause of this descending dysploidy, mitotic chromosomes of P. leptostachyus (2 n = 20) were comparatively mapped by fluorescent in situ hybridization (FISH) using bacterial artificial chromosomes (BACs) and ribosomal DNA (rDNA) probes. Our results corroborated the conservation of the 5S and 45S rDNA sites on ancestral chromosomes 10 and 6, respectively. The reduction from x = 11 to x = 10 was the result of the insertion of chromosome 10 into the centromeric region of chromosome 11, supporting a nested chromosome fusion (NCF) as the main cause of this dysploidy. Additionally, the terminal region of the long arm of chromosome 6 was translocated to this larger chromosome. Surprisingly, the NCF was accompanied by several additional translocations and inversions previously unknown for the genus, suggesting that the dysploidy may have been associated to a burst of genome reorganization in this otherwise stable, diploid plant genus.